(untitled) (Indian Journal of Public Health Research & Development, 2020)
Cervical cancer is currently ranked among the top among the various types of cancer that causes death in women in the world. The majority of women diagnosed with cervical cancer do not perform screening tests or do not follow up after being found abnormal results. The purpose of this study was to determine the correlation between cues to action or trigger and the implementation of early detection of cervical cancer using Visual Inspection with Acetic Acid (VIA) method in Kediri, Indonesia. This study used a casecontrol design. The sampling technique was a multi-stage random sampling method. The sample was 410 respondents. The data were analyzed using logistic regression. The results showed that the trigger affects the implementation of early detection of cervical cancer using the VIA method. Based on the results, the Odds Ratio (OR) cues to action or trigger values were: 1) Information from high television was obtained OR value: 2.7; 2) Recommendation from high physician was obtained OR: 2,3; 3) Recommendation from midwife was obtained OR: 2.6; 4) The recommendation from a friend was obtained OR: 2.5; 5) Having ever seen high cervical cancer patients was obtained OR: 1.6; 6) Having ever read a book or a high leaflet was obtained OR: 1.8. It showed that the higher cues to action or trigger were given to the women, the higher the probability of women to perform the early detection of cervical cancer using the VIA method. Based on the results, the appropriate cues to action or trigger need to be selected to improve the behavior of early detection of cervical cancer VIA method in women.